Homology in Structural and Functional Organization of the Fibrous Framework of the Derma and Paraneural Connective Tissue Components - Anastasia M. Dzharu; Ekaterina S. Mishina; Mariya A. Zatolokina; Karina M. Borodina; Maksim S. Novikov; Ludmila M. Kachmarskaya (International Journal of Biomedicine, 2022)
Background: The recent increase in hostilities throughout the globe is one of the main factors that damage both the skin and peripheral nerves (PN), mainly of the upper and lower extremities. The duration of treatment of the injured limb and the rate of recovery of its functions are directly related to the structural integrity of the connective tissue (CT) sheath apparatus of the PN, which further actualizes the study of its micromorphological components. The structural integrity of the peripheral nerve includes not only the preservation of its conductive component but also the membranes surrounding it, providing complete morphofunctional unity. Thus, the study of the features of their tissue organization, vascularization and innervation, with the obligatory comparison of data with homologous tissue of different topography and possible extrapolation of data, determined the purpose of this work. The aim of this study was to analyze the dynamics of changes in the fibrous components of the paraneurium and dermis in onto- and phylogenesis under the influence of various factors and to compare the data obtained for their further extrapolation. Methods and Results: The study was conducted on mature male Wistar rats under standard vivarium conditions. The material for the study was the CT sheaths of the PN of the extremities and skin areas, 1x1 cm in size, to the depth of the subcutaneous fascia of animals. The cadaver material was taken on Days 1, 3, 7, 10, and 28 of ontogeny. The resulting biomaterial was fixed in a 10% buffered neutral formalin solution and embedded in paraffin, according to the standard method. Microtomized, the resulting histological sections were stained with hematoxylin and eosin, according to the method of Mallory and Van Gieson. A comprehensive morphological study was performed using light and electron microscopy. The study revealed the presence of two stages in the ontogeny of the CT, forming the dermis of the skin and paraneural CT structures of PN. In the first stage, structural elements are formed, considering the topography of the CT; in the second, they are differentiated, leading to a qualitative-quantitative transformation due to the appearance of a number of additional functions, an active period of body growth, and taking into account the action of various environmental factors. At earlier stages of ontogenesis, thin, flattened fibrous structures without a clear organization are observed in the field of view in the dermis of the skin. In the paraneurium, the components that form it are not sufficiently expressed. At later periods, the shape and architectonics of the fibrous component change, structurization and an increase in the thickness of the fibers occur and pronounced heterogeneity of the cellular component is observed.